The welfare state reader - Pierson, Christopher; Castles, Francis G.; Naumann, Ingela K. (Cambridge : Polity Press, 2014)
The Welfare State Reader has established itself as a vital source of outstanding original research since its original appearance in 2000.
Includes bibliographical references and index.
Keywords: Welfare state; Vatandaşlık hakları; Economics -- ukslc; Sosyal devlet; Refah devlet